Research prospects of satellite to satellite electron content. - Hochegger, G.; Leitinger, R. (Física de la Tierra, 2000)
The experimental set-up we deal with is reception onboard satellites un Low Earth Orbits (LEOs) of radio signals transmitted from satellites. Plasma propagation effects allow to derive the satellite to satellite electron content. The research prospects of this quantity can be divided into two branches: investigation of the ionosphere by making use of the occultation situation and investigation of te plasmaspbere. Wc concentrate on te occultation branch and discuss evaluation possibiities and their prospects for te future. Classical inversion of the satellite to satellite electron content which is observed when tite perigee of tite radio link (ray) sinks from tite orbital height of te receiver satellite to te ground or when it rises from ground occultation gives horizontally averaged height profiles of electron density. Assessment studies have been carried out to demonstrate the usefulness and the shortcomings of inversion results. Additional data or information about horizontal gradients of the electron density in the ionosphere offers several possibilities to improve tite results. We discuss «Model Assisted Inversion» and «Tomographic Reconstruction».